Pacey Packer, unicorn tracker. 1 - Phillipps, J. C. (Julie C.) (New York : Random House, 2020)
Twelve-year-old Pacey travels through Rundalyn to rescue her little sister, Mina, who was taken there by Slasher, her unicorn-turned-plush toy, who hopes to regain his rightful form and place in society.
School Library Journal, November 2020
3-6
GN220L
3.7
Keywords: Toys -- Comic books, strips, etc. -- Juvenile fiction; Unicorns -- Comic books, strips, etc. -- Juvenile fiction; Sisters -- Comic books, strips, etc. -- Juvenile fiction; Kidnapping -- Comic books, strips, etc. -- Juvenile fiction; Babysitters -- Comic books, strips, etc. -- Juvenile fiction; Fantasy comic books, strips, etc; Adventure stories; Toys -- Fiction; Unicorns -- Fiction; Sisters -- Fiction; Kidnapping -- Fiction; Babysitters -- Fiction; Fantasy comics; Action and adventure comics; Graphic novels; Comics (Graphic works)